Pengaruh Variasi Ukuran Mesh dan Kecepatan Pengadukan Terhadap Kinerja Serat Fiber Kelapa Sawit Tanpa Aktivasi dalam Penurunan COD dan Perubahan pH Effluent POME dengan Tawas dan PAC - Fithry, Dwi Anissa; Sitorus, Oby Vijay; Syafitri, Fadila (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Palm Oil Mill Effluent (POME) has very high COD (26,420 mg/L) and acidic pH (5.25), requiring a simple, economical, and sustainable polishing stage to approach environmental quality standards. This study investigates the effect of mesh size variation and stirring speed on the performance of unactivated oil palm fiber as a polishing medium for POME effluent with alum and PAC addition to reduce COD and modify pH. Laboratory-scale batch experiments used POME effluent from PKS Sei Pagar (COD 26,420 mg/L, pH 5.25), pyrolyzed oil palm fiber (yield 63.12%, moisture 4.88%) with mesh sizes 60 and 70, stirring at 50-100 rpm for 30 minutes, and alum/PAC solution (5 g/250 ml) at 4 ml/100 ml POME. The mesh 60 + alum 100 rpm combination achieved the highest COD reduction of 54.4% and relatively stable final pH.